2009
DOI: 10.4028/www.scientific.net/msf.620-622.545
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Nanocrystallization Method on Fatigue Strength of TA2

Abstract: The enhancement of the fatigue strength is significant for the engineering applications of commercial pure titanium and its alloys. The paper investigated improvement of fatigue strength for commercial pure titanium by combined high-energy shot peening. Firstly, nano-crystallization in surface layer of pure titanium was carried out by high-energy shot peening, and then the shot peening with small diameter shots was introduced to degrade the surface roughness, enhancing the quality of the nano-grained surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The results are aligned with the few data available in the literature about the fatigue strength improvement of surface NC notched specimens, that although are quite disperse in terms of material, specimen geometry, surface NC process and test type, have all indicated of fatigue life improvement through surface nanocrystallization [16][17][18].…”
Section: Fatigue Testssupporting
confidence: 51%
See 2 more Smart Citations
“…The results are aligned with the few data available in the literature about the fatigue strength improvement of surface NC notched specimens, that although are quite disperse in terms of material, specimen geometry, surface NC process and test type, have all indicated of fatigue life improvement through surface nanocrystallization [16][17][18].…”
Section: Fatigue Testssupporting
confidence: 51%
“…Repeening using low energy small shots was applied to decrease the surface roughness up to 40%. Comparing with the fatigue limit of NP specimens, the results were increased up to 9% by CSP, up to 34% by HESP and up to 52% after repeening [18].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In this research, it is clearly showed that the pin-on-disc wear under heavy loads involves not only the surface scuffing, but also contact fatigue behavior. In addition to the compressive residual stress, USP treatment also introduced a worsening of the surface roughness, which will reduce the scratch resistance and facilitate crack initiation under fatigue loading [29,30]. Despite this, the severely deformed compound-free nitrided layer presented desirable wear resistance especially under heavy loads and the most important characteristic of the layer is the comprehensive performance supporting by the high hardness, toughness and the significantly enhanced residual compressive stress.…”
Section: Wear Characteristicsmentioning
confidence: 99%
“…Weld toe grinding can effectively improve fatigue strength of a welded joint [ 13 , 14 ], but static strength may decrease after grinding. Shot peening is one of the most widely used surface enhancing methods to improve fatigue strength [ 15 , 16 , 17 ]. Fatigue properties of the parent metal treated by shot peening have been documented in detail by Bagherifard et al and Hassani-Gangaraj et al .…”
Section: Introductionmentioning
confidence: 99%